Key Technology Design of Variable Gauge Running System for 400 km/h High-speed EMU - Dianmai ZHOU; Bin XU; Zhihui HUANG; Xiaochao DAI; Fang XU (机车电传动)
In order to adapt to different gauge sizes, based on the wheel set structure of the traditional EMU, the key technology design of the 400 km/h high-speed EMU variable gauge running system was carried out, including the clearance design of wheel and axle, the lateral locking mechanism design of wheel and axle, the transmission technology design of torque, the design of ground device, and dynamic analysis of high-speed operation. The design principles and key functions of various technologies were described in detail, which could provide ideas for the design of domestic variable gauge bogies.